STRATEGI PENGEMBANGAN DINAS PARIWISATA KABUPATEN LAMPUNG TIMUR DALAM PENGEMBANGAN OBJEK WISATA GOA PANDAN - Wahyu Widodo; Mirnawati Mirnawati; Sigit Setioko; Rizki Nirmala; Sutiyo (Nusantara Hasana Journal, 2023)
East Lampung Regency is one of the regencies in Lampung Province that has potential in the tourism sector. The tourism sector is a sector that has the potential to be developed as a source of local revenue. However, in its development efforts there are various obstacles. This research was conducted at the Goa Pandan Tourism object and related agencies, namely the East Lampung Regency Tourism Office and related stalkholders. The Pandan Cave tourist attraction has the potential to be used as a natural cruising and educational tourism object. Goa Pandan has its own characteristics that make it unique compared to other tourist objects in East Lampung Regency. This study aims to determine the potential and strategy description of Goa Pandan tourism object development. In this study, the author uses a type of qualitative research with a descriptive approach. Research informants were determined purposively. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques were carried out by data reduction, data presentation, conclusion drawing and data triangulation. Data are presented and analyzed descriptively. The results showed that the East Lampung Regency Tourism Office had a strategy to develop Pandan Cave tourism objects. There are four factors that form the basis for determining the strategy for developing the Pandan Cave tourist attraction. The four factors are strengths, weaknesses, opportunities and threats with the involvement of the community and the Giri Mulyo Village Tourism Awareness Group as tourism business actors whose maximum benefit of tourism activities is intended for the community. The conclusion of this study based on the analysis of these four factors resulted in 4 strategies, namely the S-O Strategy, the W-O Strategy, the S-W Strategy and the W-T Strategy.